The Power of Customer Service in an Academic Setting...National Society of Allied Health (NASH) Annual Conference (Virtual), March 4-6, 2021. - Cooper, L. S. (Journal of the National Society of Allied Health)
The effective delivery of excellent customer service is a critical component to the viability and longevity of any organization, more specifically to educational institutions. The importance and significance of customer service in educational institutions have become a key indicator used by administrative and governing boards to measure teaching effectiveness and the quality of student experiences. Moreover, the concept of customer service has been associated with student success, consequently, one of the primary premises for which educational institutions are funded. The purpose of this model is to provide best-practice activities and strategies adopted by Florida A&M University School of Allied Health Sciences and to provide insight into the various opportunities that can foster an environment that demonstrates continual quality customer service. The customer service model covers the following: Environmental Scan and Needs Assessment; Alignment with Standards (State/Governing Entity, Accreditation, University Administration); Importance of Establishing a Standing Customer Service Committee; Faculty/ Staff Buy-in; Strategies and Timing; Resources/Tools; Current Students and Alums; and Continuous Quality Improvement.